Improved dielectric properties achieved by blending PP and PVDF. Issue 2 (12th April 2019) - Fan, Benhui; He, Delong; Liu, Yu; Zhou, Mingyu; Zhang, Chong; Bai, Jinbo
Abstract : Polymer films composed of polypropylene (PP) and poly(vinylidene fluoride) (PVDF) have been fabricated by extrusion with filming system. Owing to the low content of crystallites and the lubricant of carbon black, the commercial product PVDF 370 can be compatible with PP by simply blending at the molten state and the obtained film has improved dielectric constant ( ɛ ′ = 4.5) and reduced dielectric loss (tan δ = 0.5%) at 1000 Hz. The modified dielectric properties result from the high dielectric constant of PVDF and low dielectric loss of PP. In addition, by introducing the third polymer, low‐density polyethylene (LDPE), the dielectric constant of the ternary blends (PP/PVDF 370/LDPE) can further be increased.